2020
DOI: 10.1177/0022466920961085
|View full text |Cite
|
Sign up to set email alerts
|

Paraprofessionals’ Perceptions of Behavior Problems in Elementary School Classrooms

Abstract: Paraprofessionals are increasingly being hired to support students with special needs in schools and are key implementers of behavior interventions for students. However, research is limited on how paraprofessionals perceive the management of student behavior. Using a mixed-methods design approach, the current investigation assesses paraprofessionals’ perceptions of common student behavior problems in elementary school classrooms. Results indicate coached paraprofessionals had a greater likelihood of reporting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The BOSS is a systematic observation tool that has consistently yielded high interobserver agreement (Volpe et al, 2005). Behavior coding was based on the Bronstein et al (2020) behavioral coding scheme. Selective codes for the training‐based “other” questions were defined through the initial coding sheet and a review of training topics frequently covered in education.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The BOSS is a systematic observation tool that has consistently yielded high interobserver agreement (Volpe et al, 2005). Behavior coding was based on the Bronstein et al (2020) behavioral coding scheme. Selective codes for the training‐based “other” questions were defined through the initial coding sheet and a review of training topics frequently covered in education.…”
Section: Methodsmentioning
confidence: 99%
“…Without sufficient training and support, paraprofessionals will utilize less effective strategies to foster learning and behaviors. For example, Bronstein et al (2020) have found that paraprofessionals are more likely to engage in reactive, consequent control strategies (e.g., reprimands, time outs) than proactive behavior management strategies (i.e., antecedent modifications, behavior praise). Research‐based PD approaches are needed to further paraprofessional knowledge and behavior support skills for students with disruptive behaviors in classroom settings (Reddy et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The issue of teachers addressing the problem of disruptive behavior in the classroom of students with learning disabilities is urgent (Gustems-Carnicer et al 2019). The Briana Bronstein et al (2020) study states that 43% disruptive behaviors of students with learning disabilities reported are "disrespectful behavior" defined as behavior of conduct or not doing something, such as "not following instructions," "absent," "unfocused," "lack of focus,". Special education students with learning disabilities in primary school more often cause disruptive behaviors such as disciplinary offenses, interrupting classes, receiving comments from teachers, and often being called by school headteachers for disciplinary offenses (Zakopoulou et al 2018).…”
Section: Literature Reviewmentioning
confidence: 99%